Kant’s Four Political Conditions<subtitle>Barbarism, Anarchy, Despotism, and Republic</subtitle> - Helga Varden (Norsk Filosofisk Tidsskrift)
In Kant’s “Doctrine of Right” there is a philosophical and interpretive puzzle surrounding the translation of a key concept: Gewalt. Should we translate it as “force,” “power,” or “violence”? This raises both general questions in Kant’s legal-political philosophy as well as puzzles regarding Kant’s definitions of “barbarism,” “anarchy,” “despotism,” and “republic” as the four possible political conditions. First, I argue that we have good textual reasons for translating Gewalt as “violence”—a translation which has the advantage that it answers these questions and puzzles convincingly. Translating Gewalt as “violence” has two further, somewhat surprising advantages. It allows us to explain how human beings can be caught in situations with no morally good ways out, and it gives us an ideal Kantian refutation of the death penalty. I then explore Kant’s account of the establishment of public authorities by means of an analogy between the birth and development of a natural person (a human being) and an artificial one (a state). This analogy helps to clarify the difference between the necessary coercive element involved in ideally establishing a state and the likely violence involved in actually establishing one. The third and final section uses the ideas of barbarism, anarchy, despotism, and republic to identify four different types of political forces operating at any given time in actual historical societies. Once we use Kant’s theory to improve our understanding of the various challenges our historical societies present, we also realize the importance and usefulness of philosophical precision when we translate Gewalt as “violence” and correctly define barbarism, anarchy, despotism, and republic.